Perancangan Sistem Otomatis Pendeteksi Perawatan Sarana Kereta Api - Rachman, Natriya Faisal; Darmawan, Arief (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
The use of android now not only acts as a means of communication for the community, but also very active role in the dissemination of information quickly and easily. With the current situation which is very practical, in this study, the design of a motorcycle safety history database was designed using android-based QRcode method. Because previously the executor still used the check list sheet, with the design of the Android-based barcode method, the executor did not need to see the data in the archive or add data through the check list sheet. The design of the andoid-based money order motor maintenance database was made in three stages, namely the creation of a database using Firebase. Making android as an interface using Android Studio and making code scanning with QRcode. Data displayed in real time, i.e. data can update data by other devices automatically so that data can be recorded and stored. Data can be opened on more than two devices that have an application installed, provided that the device must scan the QRcode. From the results of testing of the database design that has been made, it can be concluded that the android-based database system can speed up the process of data retrieval compared to taking attendance manually which is the archive of maintenance results. This system can only be used if the device used is on an internet network connection.